Tempos de tunelamento - Bonin, C. A [UNESP] (2007)
In this dissertation we show a review about the most discussed deﬁnitions of quantum tunelling times in the context of Nonrelativistic Quantum Mechanics, we propose a relativistic generalization for one of them and compare our results with those well-known ones